Analysis of goal scoring opportunities in elite male ice hockey in relation to tactical and contextual variables - Lignell, E.; Rago, V.; Mohr, M. (International Journal of Performance Analysis in Sport, 2020)
We sought to examine whether goal scoring opportunities (GSO) in elite ice hockey was affected by tactical and contextual variables. An ice hockey specific notational match analysis instrument was applied to collect 4886 GSO from 192 competitive games in the top Swedish tier. Data were collected from one elite male team and its opponents during three consecutive competitive seasons. All GSO were categorised in tactical and contextual variables. In total, 13.2% (644) of all GSO (4886) resulted in a goal. Two logistic regressions were conducted to examine the impact of tactical and contextual variables on the outcome of GSO. The multivariate analysis demonstrated higher probability to score when shooting from an area close to the goal (OR [95%CI]=.54 [.42-.69]; p <.01). Additionally, differences in numbers of involved players in specific positions, both forwards and defenders affected the probability to score a goal (p <.05) and that the probability to score from a GSO was higher in second (OR [95%CI]=1.35 [1.02-1.79]; p<.05) and third (OR [95%CI]: 1.38 [1.04-1.83], p <.05) compared to first game-period. Summarised, the study provides an insight of how goal scoring is impacted by several tactical and contextual variables.